TIPE2 May Target the Nrf2/HO-1 Pathway to Inhibit M1 Macrophage–Related Neutrophilic Inflammation in Asthma - Shi, Bingqing; Hao, Yuqiu; Li, Wei; Dong, Hongna; Xu, Mengting; Gao, Peng (Frontiers in Immunology, 2022)
Purpose Although recent studies have highlighted the link of TIPE2 and asthma airway inflammation, its roles and molecular mechanisms in different asthma inflammatory phenotypes remain largely unknown. We evaluated sputum TIPE2 expression level and its correlation with different asthma phenotypes. Additionally, we explored the roles and mechanism of TIPE2 in M1 polarization of macrophages. Methods A total of 102 asthma patients who underwent sputum induction were enrolled to evaluate the expression level of TIPE2 and its association with different asthma phenotypes. To explore the roles and mechanism of TIPE2 in M1 polarization of macrophages, THP-1 monocytes stimulated with phorbol-12-myristate-13-acetate, were used as a model of undifferentiated (M0) macrophages, and M0 macrophages were treated with lipopolysaccharide to induce M1 macrophages. Results The sputum TIPE2 level was significantly lower in patients with neutrophilic asthma (NA) and higher in patients with eosinophilic asthma (EA) compared with patients with paucigranulocytic asthma. The levels of IL-1β, TNF-α and IL-6 were highest in NA compared with other groups. TIPE2 levels in sputum negatively correlated with IL-1β and TNF-α levels but positively correlated with IL-4, IL-5, IL-13, and IL-10 levels (P < 0.05). In vitro, TIPE2 enhanced Nrf2/HO-1 pathway activation in macrophages and inhibited LPS-induced M1 macrophage differentiation and related cytokine release. Further analysis showed that the Nrf2 inhibitor ML385 weakened TIPE2-induced activation of the Nrf2/HO-1 pathway, as well as TIPE2-induced suppression in M1 polarization of macrophage and inflammatory cytokines secretion. Conclusions TIPE2 expression level was highly down-regulated in NA and was negatively correlated with inflammatory factors (IL-1β and TNF-α). Aberrant expression of TIPE2 may target the Nrf2/HO-1 pathway to inhibit M1 macrophage–related neutrophilic inflammation in asthma.